Efficacy of sublingual immunotherapy in children with asthma and rhinitis: A double-blind, placebo-controlled study - (:unkn) unknown (WILEY-LISS, 2001)
To evaluate the efficacy of specific sublingual immunotherapy (SLIT), we enrolled 15 children with asthma and rhinitis (7 girls, 8 boys, mean +/- SD age of 11.7 +/- 3.3) allergic to house dust mite (HDM) into a double-blind, placebo-controlled study. After a run-in period, patients were randomized to receive either placebo (n = 7) or SLIT (n = 8) with a standardized Dermatophagoides pteronyssinus (D. pteronyssinus) + Dermatophagoides farinea (D. farinea) 50/50 extract. They received increasing doses up to 100 index units of reactivity (IR) every day for 4 weeks, then 100 IR/day for another 4 weeks, followed by maintenance therapy consisting of 20 drops 2 times a week for 4 months. Efficacy was assessed at the end of 6 months of therapy according to symptom and medication scores, serum total IgE levels, results of lung function tests, methacholine provocation tests, and skin prick tests. Daily means for the asthma score and use of inhaled beta-2-mimetics decreased significantly in the SLIT group (P = 0.05, P = 0.028, respectively), whereas no such difference was observed in the placebo group. At the end of follow-up, mean daily doses of intranasal steroids needed for control of rhinitis symptoms decreased significantly in the SLIT group (P = 0.04). Baseline skin sensitivity to D. pteronyssinus and D. farinea was not significantly different between in the two groups, whereas end-point wheal diameter obtained with D.pteronyssinus extract was significantly less in the SLIT vs. the placebo group (p = 0.026). At the end of 6 months, peak expiratory flow (PEF) values in the placebo group was significantly lower than in the SLIT group (P = 0.049). Throughout the treatment period, the SLIT group was found to have less asthma exacerbations than the placebo group (p = 0.007). The provocation concentration causing a 20% drop in forced expired volume in 1 sec did not change throughout the treatment period in either groups. None of the patients reported local or systemic side effects from SLIT. Results of this study suggests that SLIT may be a useful alternative or additional therapy in the treatment of children with asthma/rhinitis due to HDM. (C) 2001 Wiley-Liss, Inc.
Keywords: sublingual immunotherapy; asthma; rhinitis; house dust mite; children; HOUSE-DUST-MITE; DERMATOPHAGOIDES-PTERONYSSINUS; POLLEN EXTRACT; TRIAL; SLIT